KECEMASAN SANTRI PONDOK PESANTREN TERHADAP KASUS COVID-19 DI PONDOK PESANTREN MAMBAUL IHSAN KECAMATAN KERTANEGARA KABUPATEN PURBALINGGA - Tono Aminudin; Tophan Heri Wibowo; Ita Apriliyani; Feti Kumala Dewi (Melati Institute, 2022)
Corona Virus Disease 2019 (Covid-19) is a type of infectious disease transmitted by Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2). Anxietyunclear feeling of fear accompanied by feelings of uncertainty, insecurity, helplessness and isolation. This study aims to identify the level of Anxiety of Islamic Boarding School Students against Covid-19 Cases at Mambaul Ihsan Islamic Boarding School. The research method is descriptive research with a sampling technique using purpose sampling. This study identifies the anxiety status of students by using 20 standard questionnaire questions from Zung Self. -Rating Anxiety Scale (SAS/SRAS). The results of the research from the number of respondents 171 students aged 13-17 years, male students 53 students (31%) and female students 118 students (69%), obtained the results 167 students (97.7%) were not anxious / normal, 4 students (2.3%) mild anxiety, and no moderate or severe anxiety (0%).